2014
DOI: 10.1002/nbm.3200
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of diffuse fibrosis in the failing human heart via diffusion tensor imaging and quantitative histological validation

Abstract: Non-invasive imaging techniques are highly desirable as an alternative to conventional biopsy for characterizing remodeling of tissues associated with disease progression, including end-stage heart failure. Cardiac diffusion tensor imaging (DTI) has become an established method for characterizing myocardial microstructure. However, the relationships between diffuse myocardial fibrosis, which is a key biomarker for staging and treatment planning of the failing heart, and measured DTI parameters have yet to be s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
40
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(49 citation statements)
references
References 59 publications
9
40
0
Order By: Relevance
“…(iii) The results question the use of DTI in microstructural studies of cardiac samples exposed to formalin for a prolonged period that exceeds 6 weeks prior to imaging. In fact, there are numerous ex vivo cardiac DTI studies, where the specimens remained in formalin for a prolonged period (for example, over a month in (Jiang et al, ; Abdullah et al, ), 6 months in (Mazumder et al, ), over a year in (Eggen et al, ), to name a few) prior to imaging. According to the findings of this article, caution should be exercised in adopting the results from such studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(iii) The results question the use of DTI in microstructural studies of cardiac samples exposed to formalin for a prolonged period that exceeds 6 weeks prior to imaging. In fact, there are numerous ex vivo cardiac DTI studies, where the specimens remained in formalin for a prolonged period (for example, over a month in (Jiang et al, ; Abdullah et al, ), 6 months in (Mazumder et al, ), over a year in (Eggen et al, ), to name a few) prior to imaging. According to the findings of this article, caution should be exercised in adopting the results from such studies.…”
Section: Discussionmentioning
confidence: 99%
“…The bases for this assumption were: (i) Histology‐based experimental observations (Fox et al, ) that the tissue reaches an equilibrium state after the initial crosslinking actions, and (ii) former findings from some individual non‐cardiac longitudinal studies (Kim et al, ; Dyrby et al, ) demonstrating stability of DTI parameters over a prolonged (namely, several weeks for cervical spinal cord and 3 years for brain) period of tissue exposure to formalin. A recent cardiac DTI study (Watson and Hsu, ) that aimed at evaluating the effects of fixation duration on DTI parameters showed that, after some initial changes (that took place the first 48 hr following the tissue immersion in the formaldehyde‐based solution), the DTI parameters remained stable for up to 7 days; however, it happens frequently (Jiang et al, ; Eggen et al, ; Mazumder et al, ; Abdullah et al, ) that the cardiac tissue is exposed to formalin for a much more prolonged period prior to imaging.…”
mentioning
confidence: 99%
“…We extend this finding to less focal and more subtle, myocardial fibrosis present in the elderly rat hearts. Diffuse fibrosis present in the heart, from various etiologies, has been identified with CMR T 1 mapping, ECV, and DTI methods [10, 13, 1521, 34]. Moreover the increase of collagen content in the aging heart has been studied in animal models [3, 34–37] and patients [3, 12, 38] using these emerging CMR imaging techniques.…”
Section: Discussionmentioning
confidence: 99%
“…The advantage of these methods is the absolute scale to measure these myocardial tissue properties. CMR diffusion tensor imaging (DTI) has been explored in patients with heart failure to characterize the myocardial microstructure in the presence of diffuse fibrosis [21]. Alternatively, T 2 measurements have been successful in detecting diffuse myocardial fibrosis [22].…”
Section: Introductionmentioning
confidence: 99%
“…Contrast‐free quantitative cardiac MR techniques have been demonstrated to be promising for evaluating replacement myocardial fibrosis in chronic myocardial infarction. Diffusion‐weighted imaging (DWI) has been histologically validated in detecting regions of myocardial fibrosis in MI scar tissue and diffuse myocardial fibrosis in the failing heart . Additionally, some studies reported the feasibility and prognostic value of DWI in the characterization of diffuse myocardial fibrosis via correlation with the ECV value .…”
mentioning
confidence: 99%